Development of Macca Biology Learning Media Based on Android Software Andromo - Muhammad Arafah; Arman Arifuddin; Andi Badli Rompegading; Rizal Irfandi; Muhammad Nur; Muhammad Kemal Nasser P; Ahmad Yani; Syamsu Rijal; Ambo Upe (Postgraduate, University of Mataram, 2023)
The purpose of this study is to evaluate the applicability, efficacy, and validity of Macca Biology Learning Media, which is based on Andromo Android Software, for environmental pollution content in Class VII SMP Negeri 3 Sengkang. The research methodology employed is research and development, also known as define, design, and development (3D model research and development). This study involved 32 students in class VII and was conducted during the even semester of the 2022–2023 academic year, which began in February–March 2023. The teacher and student practicality questionnaire, student learning outcomes, and validator results provided the research data. A % quantitative descriptive method was used to process the study's results. Macca Biology Learning Media received 90.5% from the media and material validators, 91.6% from the teacher's practical responses and 90.5% from the students' practical responses, and 96.8% of the students received a perfect score from the learning outcomes, according to the study's findings. The study's findings indicate that the Macca Biology Learning Media, which utilizes the Andromo Android platform, is a reliable, useful, and efficient resource for biology education.